2012
DOI: 10.1186/1477-3155-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of gold and silver nanoparticles against Escherichia coli and bacillus Calmette-Guérin

Abstract: BackgroundDiseases such as tuberculosis (TB) have always had a large impact on human health. Bacillus Calmette-Guérin (BCG) is used as a surrogate for TB during the development of anti-TB drugs. Nanoparticles (NPs) have attracted great interest in drug development. The purpose of this study was to examine the potential of NPs as anti-TB compounds by studying the interacting mechanisms between NPs and bacteria.ResultsWe investigated effects of gold and silver NPs on BCG and Escherichia coli. Experimentally, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
286
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(299 citation statements)
references
References 17 publications
11
286
2
Order By: Relevance
“…The antimicrobial activity of the nanoparticles is attributed to their attachment to microbial cell membranes, followed by alteration of membrane potential, decrease of ATP level and inhibition of tRNA binding to the ribosome (Cui et al 2012). However, particles can aggregate when weakly bound capping agents like citrate are used, which leads to reduced surface area and decreased interactions with the nanoparticles (Zhou et al 2012). In contrast, gold nanoparticles with the same shape and size but capped with strongly bound agent may exhibit enhanced antimicrobial properties (Zhou et al 2012;Dizaj et al 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The antimicrobial activity of the nanoparticles is attributed to their attachment to microbial cell membranes, followed by alteration of membrane potential, decrease of ATP level and inhibition of tRNA binding to the ribosome (Cui et al 2012). However, particles can aggregate when weakly bound capping agents like citrate are used, which leads to reduced surface area and decreased interactions with the nanoparticles (Zhou et al 2012). In contrast, gold nanoparticles with the same shape and size but capped with strongly bound agent may exhibit enhanced antimicrobial properties (Zhou et al 2012;Dizaj et al 2014).…”
mentioning
confidence: 99%
“…However, particles can aggregate when weakly bound capping agents like citrate are used, which leads to reduced surface area and decreased interactions with the nanoparticles (Zhou et al 2012). In contrast, gold nanoparticles with the same shape and size but capped with strongly bound agent may exhibit enhanced antimicrobial properties (Zhou et al 2012;Dizaj et al 2014). The antimicrobial activity of zinc oxide nanoparticles is due to contact between nanoparticles and pathogen cells, which alters surface charges and electrostatic interactions (Stoimenov et al 2002;Neal, 2008;Zhang et al 2010), leading to rupture of the cell membrane (Zhang et al 2007;Jiang et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, silver nanoparticles have been preferred because of their antimicrobial effect to fight against infection and diseases (Ravindra et al, 2012). Silver exhibits strong cytotoxicity for various microorganisms and it has been extensively used to control infections since ancient times (Travan et al, 2009;Pinto et al, 2009;Zhou et al, 2012). Metallic and ionic forms of silver have a bacteriostatic (growth inhibition) or a bactericidal (antibacterial) impact (Pinto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nano-based drug delivery systems have attracted the attention of many research groups, which concluded that metal nanoparticles as gold and silver could be promising noble nanomaterials in biomedicine and drug delivery [13][14][15]. However the gold and silver nanoparticles have shown antimicrobial activities against Gram-negative and Grampositive bacteria [16,17], they revealed antimycobacterial activities against extracellular TB [18]. Other different nanoparticles were investigated in vitro and in vivo as drug delivery vehicle for anti-TB drugs.…”
Section: Introductionmentioning
confidence: 99%